Cutting-edge knowledge on the roles of phytobiotics and their proposed modes of action in swine - Sriniwas Pandey; Eun Sol Kim; Jin Ho Cho; Minho Song; Hyunok Doo; Sheena Kim; Gi Beom Keum; Jinok Kwak; Sumin Ryu; Yejin Choi; Juyoun Kang; Jeehwan Choe; et al. (Frontiers in Veterinary Science, 2023)
With the ban on antibiotics in the swine industry, the exploration of alternative options has highlighted phytobiotics as a promising substitute for antibiotic growth promoters, aiming to foster a more sustainable swine industry. Phytobiotics are non-nutritive natural bioactive components derived from plants that offer numerous health benefits. They exhibit antioxidative, antimicrobial, and anti-inflammatory effects. Phytobiotics can be utilized in various forms, including solid, dried, ground, or as extracts, either in crude or concentrated form. They are characterized by low residual levels, a lack of resistance development, and minimal adverse effects. These qualities make phytobiotics an attractive choice for enhancing health and productivity in swine, presenting them as a viable alternative to antibiotics. While there is a general understanding of the effects of phytobiotics, there is still a need for detailed information regarding their effectiveness and mechanisms of action in practical settings. Therefore, the purpose of this mini review was to summarize the current knowledge supporting the roles of phytobiotics and their proposed modes of action, with a specific focus on swine.